Knocking Down TcNTPDase-1 Gene Reduces in vitro Infectivity of Trypanosoma cruzi - Silva-Gomes, Natália Lins; Rampazzo, Rita de Cássia Pontello; Moreira, Claudia Maria do Nascimento; Porcino, Gabriane Nascimento; Santos, Cyndia Mara Bezerra dos; Krieger, Marco Aurélio; Vasconcelos, Eveline Gomes; Fragoso, Stenio Perdigão; Moreira, Otacilio C. (Frontiers in Microbiology, 2020)
Ecto-Nucleoside Triphosphate Diphosphohydrolases are enzymes that hydrolyze tri- and/or diphosphate nucleosides. Evidences pointed out to their participation in Trypanosoma cruzi virulence, infectivity and purine acquisition. In this study, recombinant T.cruzi knocking out or overexpressing the TcNTPDase-1 gene were built, and the role of TcNTPDase-1 in the in vitro interaction with VERO cells was investigated. Results show that epimastigote forms of hemi-knockout parasites showed about 50% lower level of TcNTPDase-1 gene expression when compared to the wild type, while the T.cruzi overexpressing this gene reach 20 times higher gene expression. In trypomastigote forms, the same decreasing in TcNTPDase-1 gene expression was observed to the hemi-knockout parasites. The in vitro infection assays showed a reduction to 51.6% and 59.9% at the adhesion and to 25.2% and 26.4% at the endocytic indexes to the parasites knockout to one or other allele (Hygro and Neo hemi-knockouts), respectively. In contrast, the infection assays with T.cruzi overexpressing TcNTPDase-1 from the WT or Neo hemi-knockout parasites showed an opposite result, with the increasing to 287.7% and 271.1% at the adhesion and to 220.4% and 186.7% at the endocytic indexes, respectively. The parasitic load estimated in infected VERO cells by quantitative real time PCR corroborated these findings. Taken together, the partial silencing and overexpression of the TcNTPDase-1 gene generated viable parasites with low and high infectivity rates, respectively, corroborating that the enzyme encoded for this gene plays an important role to the T.cruzi infectivity.